Reliable Load Balanced Routing Policy using Bayesian Optimization for SDN-IOT Applications - Srinivasan, G.; Sekhar, G. Seshadri; Suresh, P. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In this paper, we propose to design the reliable load balancing routing policy using Bayesian optimization for Software Defined Network (SDN) and Internet of Things (IoT) heterogeneous applications. The main aim of this approach is to determine the best path between the IoT gateway and the target IoT server while satisfying the servers’ resource limits as well as Quality of Service (QoS) requirements of traffic like lower delay and higher throughput. For delay-aware traffic, the controller selects the forwarder nodes with lower delay and lower packet queue length. For bandwidth-aware traffic, the link quality, link capacity and noise parameters are estimated and the forwarder nodes with high link capacity and quality with lower noise will be selected. For normal traffic, shortest path will be selected. Then by applying Bayesian optimization, the optimum load balanced path is selected for each type of traffic. By simulation results, it has been shown that the proposed technique enhances the network throughput and minimizes the end-to-end delay.